Evidence summaries and recommendations from the international evidence-based guideline for the assessment and management of polycystic ovary syndrome: assessment and treatment of infertility. Issue 1 (4th January 2019) - Costello, M F; Misso, M L; Balen, A; Boyle, J; Devoto, L; Garad, R M; Hart, R; Johnson, L; Jordan, C; Legro, R S; Norman, R J; Mocanu, E; et al.
Abstract: STUDY QUESTION: What is the recommended assessment and management of infertile women with polycystic ovary syndrome (PCOS), based on the best available evidence, clinical expertize and consumer preference? SUMMARY ANSWER: International evidence-based guidelines, including 44 recommendations and practice points, addressed prioritized questions to promote consistent, evidence-based care and improve the experience and health outcomes of infertile women with PCOS. WHAT IS KNOWN ALREADY: Previous guidelines on PCOS lacked rigorous evidence-based processes, failed to engage consumer and multidisciplinary perspectives or were outdated. The assessment and management of infertile women with PCOS are inconsistent. The needs of women with PCOS are not being adequately met and evidence practice gaps persist. PARTICIPANTS/MATERIALS, SETTING, METHODS: Governance included a six continent international advisory and a project board, a multidisciplinary international guideline development group (GDG), consumer and translation committees. Extensive health professional and consumer engagement informed the guideline scope and priorities. The engaged international society-nominated panel included endocrinology, gynaecology, reproductive endocrinology, obstetrics, public health and other experts, alongside consumers, project management, evidence synthesis and translation experts. Thirty-seven societies and organizations covering 71 countries engaged in the process. Extensive online communication and two face-to-face meetings over 15 months addressed 19 prioritized clinical questions involving nine evidence-based reviews and 10 narrative reviews. Evidence-based recommendations (EBRs) were formulated prior to consensus voting within the guideline panel. STUDY DESIGN, SIZE, DURATION: International evidence-based guideline development engaged professional societies and consumer organizations with multidisciplinary experts and women with PCOS directly involved at all stages. A (AGREE) II-compliant processes were followed, with extensive evidence synthesis. The Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) framework was applied across evidence quality, desirable and undesirable consequences, feasibility, acceptability, cost, implementation and ultimately recommendation strength. The guideline was peer-reviewed by special interest groups across our partner and collaborating societies and consumer organizations, was independently assessed against AGREE II criteria and underwent methodological review. This guideline was approved by all members of the GDG and has been approved by the NHMRC. MAIN RESULTS AND THE ROLE OF CHANCE: The quality of evidence (QOE) for the EBRs in the assessment and management of infertility in PCOS included very low ( n = 1), low ( n = 9) and moderate ( n = 4) quality with no EBRs based on high-quality evidence. The guideline provides 14 EBRs, 10 clinical consensus recommendations (CCRs) and 20 clinical practice points on the assessment and management of infertility in PCOS. Key changes in this guideline include emphasizing evidence-based fertility therapy, including cheaper and safer fertility management. LIMITATIONS, REASONS FOR CAUTION: Overall evidence is generally of low to moderate quality, requiring significantly greater research in this neglected, yet common condition. Regional health systems vary and a process for adaptation of this guideline is provided. WIDER IMPLICATIONS OF THE FINDINGS: The international guideline for the assessment and management of infertility in PCOS provides clinicians with clear advice on best practice based on the best available evidence, expert multidisciplinary input and consumer preferences. Research recommendations have been generated and a comprehensive multifaceted dissemination and translation program supports the guideline with an integrated evaluation program. STUDY FUNDING/COMPETING INTEREST(S): The guideline was primarily funded by the Australian National Health and Medical Research Council of Australia (NHMRC) supported by a partnership with ESHRE and the American Society for Reproductive Medicine (ASRM). GDG members did not receive payment. Travel expenses were covered by the sponsoring organizations. Disclosures of conflicts of interest were declared at the outset and updated throughout the guideline process, aligned with NHMRC guideline processes. Dr Costello has declared shares in Virtus Health and past sponsorship from Merck Serono for conference presentations. Prof. Norman has declared a minor shareholder interest in the IVF unit Fertility SA, travel support from Merck and grants from Ferring. Prof. Norman also has scientific advisory board duties for Ferring. The remaining authors have no conflicts of interest to declare. This article was not externally peer-reviewed by Human Reproduction Open.